Competence, Work Engagement, Perceived Organizational Support on Employee Performance with Organizational Citizenship Behavior as Mediation Variables - Palupi, Dian; Amanah, Lailatul; Rochdianingrum, Widhi Ariestianti (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study analyzed the impact of competence, work engagement, and perceived organizational support mediated by organizational citizenship behavior. The sample in this study were employees of PT. Fortuna Laboratory Indonesia. This research was quantitative research using questionnaires distributed online. The results showed that competence, work engagement, and perceived organizational support affected employee performance. The results of other studies indicate that organizational citizenship behavior is proven to significantly mediate the effect of competence, work engagement, and perceived organizational support on employee performance. These results showed that companies must train employees to have competence as laboratory assistants and administrative staff and conduct training and seminars as a form of organizational support. In addition, employees need to be involved in organizational decision-making. Thus, they feel valued and entangled in the organization.